(untitled) (Yupana, 2020)
This work presents an analysis of the resolutions of 140 students of Statistics from the Faculty of Engineering of the Universidad Nacional de Mar del Plata. The productions arise from the comparison of data distributions that requires relating measures of central tendency and variability in a graphical and analytical way. The results obtained were studied within the framework of the Ontosemiotic Approach to Knowledge and Mathematical Instruction, identifying the mathematical practices used with some defined skills, in the Gal’s model, as components of statistical reasoning. Most of the students carried out an analysis on the location of the mean in the distribution of the data, according to symmetry and variability, but found difficulties in evidencing the statistical knowledge skills sought in the study. Almost the total of the rest of the students correctly solved the problem, translating the graphs into frequency tables, despite the incomplete information in the graphs. The obtained results warn about aspects to consider in didactic proposals that integrate the graphic and analytical analysis of the data for the development of skills according to the statistical reasoning required in engineering students.